Financování projektů z fondů EU - Bambuch, Petr (Vysoké učení technické v Brně. Fakulta podnikatelská, 2011)
Diplomová práce se zaměřuje na fondy Evropské unie, konkrétně na fond v rámci Operačního programu Podnikání a inovace. Jsou zde rozebrány možnosti financování projektů, postupy žádosti o přidělení grantu a na konkrétním příkladu je rozebráno a vyhodnoceno financování projektu za pomocí dotace z EU.

The Master's thesis focuses on European Union funds mainly on fund which is a part of the Operational Programme Business and Innovation. It deals with the options of projects financing and grant application processes. Funding of the projects using grants from the EU is analyzed and evaluated in the specific case.
Projects Financing from EU Funds
Keywords: fondy EU; dotace; projekt; financování; operační program; podnikaní a inovace; EU funds; grant; project; financing; operational program; business and innovation